Analisis Perencanaan Laba Perusahaan Melalui Penerapan Break Even Point pada PT. Semen Indonesia 2023 - Zulfiana Siti Awaliyah; Asri Jumiyati; Andini Liliyani; Maria Winona Patricia Faku (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
When it comes to setting management strategies to achieve the company's financial goals, profit planning is a crucial indicator. Using information from PT. Semen Indonesia (Persero), Tbk's 2023 annual report and consolidated financial statements, this study will analyze the effectiveness of Break Even Point in the company's profit planning process. A quantitative descriptive method using a case study approach was used by the author as their research procedure. According to the results of the research, the company earns a BEP value of Rp. 22,273,475 million rupiah and Rp. 37,169,043 tons of unit value. The firm is in good financial standing as actual sales of Rp. 38,651,360 million have exceeded the break-even point. The firm is well-protected against the risk of declining revenues, as shown by the Margin Of Safety (MOS) number of 42.37%. The Break Even Point analysis method, when used to profit target planning, reveals that the company requires record minimum sales of Rp. 30,516,912 million to achieve a net profit of Rp. 2,170,497 million. The author may draw the conclusion that Break Even Point analysis is a useful tool for profit planning and supporting strategic decisions based on these results.